2020
DOI: 10.1111/hae.13929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fully automated von Willebrand factor assay panel for the diagnosis of von Willebrand disease

Abstract: Introduction von Willebrand disease (VWD) diagnosis starts with first level tests: factor VIII coagulant activity, VWF antigen (VWF:Ag) and platelet‐dependent VWF activity (VWF:RCo, VWF:Ab, VWF:GPIbR or VWF:GPIbM). The VWF collagen binding (VWF:CB) assay measures the binding capacity of von Willebrand factor (VWF) to collagen. Aim To assess, in previously diagnosed VWD patients, the performance of a fully automated chemiluminescent test panel including VWF:Ag, VWF:GPIbR and VWF:CB assays. Methods The patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
(78 reference statements)
0
5
0
15
Order By: Relevance
“…26 We can only await further clarification of this fascinating story with additional study, in particular with emerging newer contemporary VWF methodologies, including VWF:GPIbR and VWF:GPIbM, as well as novel VWF:CB methods by chemiluminescence procedures. 6,16,18,27 I also look forward to increasing recognition of 2M VWD, and reduction in 2M VWD misdiagnosis. 13,[26][27][28]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26 We can only await further clarification of this fascinating story with additional study, in particular with emerging newer contemporary VWF methodologies, including VWF:GPIbR and VWF:GPIbM, as well as novel VWF:CB methods by chemiluminescence procedures. 6,16,18,27 I also look forward to increasing recognition of 2M VWD, and reduction in 2M VWD misdiagnosis. 13,[26][27][28]…”
mentioning
confidence: 99%
“…6,16,18,27 I also look forward to increasing recognition of 2M VWD, and reduction in 2M VWD misdiagnosis. 13,[26][27][28]…”
mentioning
confidence: 99%
“…If and when automated/semiautomated platforms become more widely available in the United States, use of these assays may increase. 13,14 We observed a positive bias relative to VWF:RCo for samples categorized as having been run with the HemosIL reagent, presumed to be mostly, if not all VWF:Ab. This affects both the activity measurements and the activity-toantigen ratios and has the potential to affect VWD classification that is based on these ratios.…”
Section: Discussionmentioning
confidence: 80%
“…If and when automated/semiautomated platforms become more widely available in the United States, use of these assays may increase. 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Jakob et al 295 included the VWF:CB in their study of VWF parameters as potential biomarkers for disease activity and coronary artery lesion in patients with Kawasaki disease, and showed a significant reduction in VWF:CB/Ag ratio in these patients. Stufano et al 296 reported their evaluation of the AcuStar VWF assay panel (VWF:Ag, VWF:GPIbR, VWF:CB) for the diagnosis of VWD. They reported similarly with our prior 2016 study, 249 with AcuStar VWF:GPIbR/Ag and VWF:CB/Ag showing overall good concordance with corresponding data obtained at the time of the historical diagnosis with earlier VWF assays.…”
Section: The Current Decade—the 2020smentioning
confidence: 99%